IoT based implemented comparison analysis of two well-known network platforms for smart home automation - Alani, Sameer; Mahmood, Sarmad Nozad; Attaallah, Sarah Zaeead; Mhmood, Haneen Sameer; Khudhur, Zeena Abdulsattar; Dhannoon, Azzam Amer (Institute of Advanced Engineering and Science, 2021)
The developments of the internet of things (IoT) technologies fascinated the universe and provided great opportunities to introduce these innovations in smart house networks. Smart home automation is highly required these days. Smart home automation is a collection of electronic devices connected to monitor and control in the market home appliance remotely. However, it is still needed to design a friendly and reliable system since the system mainly depends on the devices used and the environment of the network. NETPI and BLYNK are IoT frameworks used for hardware-agnostic with smartphones, websites, private clouds, system security, data mining, and deep learning. The results confirmed that NETPI provides flexibility to deal with several NODEMCU controllers in a single control framework. The proposed system shows its applicability in monitoring and controlling home appliances remotely.